New agents in chemotherapy of disseminated non-small cell lung cancer – real benefits - M. Kowalski, Dariusz; Krzakowski, Maciej (Contemporary Oncology/Współczesna Onkologia, 2001)
Approximately 60-65% of all patients with non-small-cell lung cancer present with either unresectable or metastatic disease. These patients are potential candidates for systemic therapy either alone or in combination with radiotherapy. Cisplatin-based combination chemotherapy has been shown to prolong survival when compared with best supportive care in patients with advanced non-small-cell lung cancer. In addition to a modest survival benefit (10% absolute improvement in one-year survival rate), platinum-based chemotherapy may reduce cancer-related symptoms and improve patients' quality of life. Over the past 10 years, several new and promising cytotoxic agents (in particular, the taxanes – paclitaxel and docetaxel, new Vinca compound – vinorelbine, and new antimetabolite – gemcitabine) have entered the therapeutic armamentarium in the treatment of advanced non-small cell-lung cancer. When used in single-agent therapy they show activity comparable with conventional multi-drug chemotherapy regimens. At least, some of the new agents (namely, vinorelbine, gemcitabine) show significantly better toxicity profiles than older multi-drug chemotherapy regimens. Interestingly, new agents produce significant benefit in patients with progressive disease previously exposed to chemotherapy. The use of several new agents in combination with cisplatin results in marginal improvements in response rates and in survival, compared with cisplatin given alone or in combination with older cytotoxic agents. The new regimens are all of approximately equal efficacy in terms of response and survival rates. The toxicity profiles of chemotherapy with new agents are comparable and the minimal differences do not have a significant impact on patients' quality of life. Other factors may be also responsible for improved response and survival rates when new agents are incorporated into combination chemotherapy for advanced non-small cell lung cancer patients, including individual selection of drugs based on specific molecular findings in particular patient, more precise diagnostic procedures and improved supportive care. Further investigational directions related to the use of new cytoxic agents should be focused on their role in the management of elderly patients as well as in individuals with compromised performance status when one can expect higher toxicity rates. Second-line chemotherapy with the use of new agents demands further studies. The studies with the new cytotoxic agents in non-small-cell lung cancer should include quality of life evaluations as well as cost-utility analysis.